2004
DOI: 10.1086/382999
|View full text |Cite
|
Sign up to set email alerts
|

The Star Formation Rate and Dense Molecular Gas in Galaxies

Abstract: HCN luminosity is a tracer of dense molecular gas, n(H 2 ) k 3 ; 10 4 cm À3 , associated with star-forming giant molecular cloud (GMC) cores. We present the results and analysis of our survey of HCN emission from 65 infrared galaxies, including nine ultraluminous infrared galaxies (ULIGs, L IR k10 12 L ), 22 luminous infrared galaxies (LIGs, 10 11 L < L IR P10 12 L ), and 34 normal spiral galaxies with lower IR luminosity (most are large spiral galaxies). We have measured the global HCN line luminosity, and th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

199
1,458
16
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 962 publications
(1,679 citation statements)
references
References 102 publications
199
1,458
16
6
Order By: Relevance
“…This is apparent in the left panel of Figure 44, where the light orange circles represent local quiescent galaxies, and the light (small) blue stars represent local starbursts. Gao & Solomon (2004b) find a slope of 1.25 − 1.44 between L IR and L CO (i.e. pure observables) when considering unresolved CO (J=1-0) observations of both local quiescent galaxies, and nearby LIRGs and ULIRGs.…”
Section: Star Formation Laws and Efficienciesmentioning
confidence: 90%
“…This is apparent in the left panel of Figure 44, where the light orange circles represent local quiescent galaxies, and the light (small) blue stars represent local starbursts. Gao & Solomon (2004b) find a slope of 1.25 − 1.44 between L IR and L CO (i.e. pure observables) when considering unresolved CO (J=1-0) observations of both local quiescent galaxies, and nearby LIRGs and ULIRGs.…”
Section: Star Formation Laws and Efficienciesmentioning
confidence: 90%
“…There is good observational evidence (e.g., Kennicutt(1998), Gao & Solomon(2004), Greve et al (2005), Bouché et al (2007)) that at higher gas columns, the relation steepens further, so that the SFR-per-H 2 ratio is higher in starburst galaxies than in normal galaxy disks. This may drive the frequent observation of N ≈ 1.5 in starburst galaxies.…”
Section: The Composite Star Formation Lawmentioning
confidence: 99%
“…Incorrect gas masses could also introduce biases in the observed Schmidt-Kennicutt relation (Schmidt 1959;Kennicutt 1989), an empirical correlation thatprobes the physical process responsible for star formation (e.g., Bigiel et al 2008 and references therein) and is frequently used as input for numerical simulations of galaxy formation (e.g., Springel & Hernquist 2003;Narayanan et al 2008a;Somerville et al 2008;Juneau et al 2009). Despite numerous studies of the Schmidt-Kennicutt relation, differences in methods (integrated versus spatially resolved studies; e.g., Young et al 1986;Solomon & Sage 1988;Buat et al 1989;Kennicutt 1998Kennicutt , 1989Gao & Solomon 2004;Bouché et al 2007;Bigiel et al 2008;Krumholz et al 2009;Bigiel et al 2010;Daddi et al 2010;Genzel et al 2010;Wei et al 2010;Tacconi et al 2013), assumptions (particularly gas mass conversion factors; e.g., Bigiel et al 2008;Daddi et al 2010;Genzel et al 2010), gas and SFR tracers (e.g., Gao & Solomon 2004;Narayanan et al 2005;Bussmann et al 2008;Graciá-Carpio et al 2008;Iono et al 2009;Juneau et al 2009;Kennicutt & Evans 2012), and galaxy populations (e.g. Gao & Solomon 2004;Daddi et al 2010;Genzel et al 2010;Tacconi et al 2013) leadto significant uncertainties in the relation's characteristics (such as the index of the power law) and interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…Despite numerous studies of the Schmidt-Kennicutt relation, differences in methods (integrated versus spatially resolved studies; e.g., Young et al 1986;Solomon & Sage 1988;Buat et al 1989;Kennicutt 1998Kennicutt , 1989Gao & Solomon 2004;Bouché et al 2007;Bigiel et al 2008;Krumholz et al 2009;Bigiel et al 2010;Daddi et al 2010;Genzel et al 2010;Wei et al 2010;Tacconi et al 2013), assumptions (particularly gas mass conversion factors; e.g., Bigiel et al 2008;Daddi et al 2010;Genzel et al 2010), gas and SFR tracers (e.g., Gao & Solomon 2004;Narayanan et al 2005;Bussmann et al 2008;Graciá-Carpio et al 2008;Iono et al 2009;Juneau et al 2009;Kennicutt & Evans 2012), and galaxy populations (e.g. Gao & Solomon 2004;Daddi et al 2010;Genzel et al 2010;Tacconi et al 2013) leadto significant uncertainties in the relation's characteristics (such as the index of the power law) and interpretation. Different molecular emission lines are sensitive to different density regimes in the ISM (Krumholz & Thompson 2007;Narayanan et al 2008bNarayanan et al , 2011, making the observed index of the Schmidt-Kennicutt relation dependent on the gas physical conditions.…”
Section: Introductionmentioning
confidence: 99%